1996
DOI: 10.5271/sjweh.141
|View full text |Cite|
|
Sign up to set email alerts
|

Reproductive effects of paternal exposure to chlorophenate wood preservatives in the sawmill industry

Abstract: Objectives The purpose of the study was to determine whether paternal occupational exposure to dioxincontaminated chlorophenols is associated with an increased risk of congenital anomalies or other adverse reproductive outcomes in offspring. Methods As a result of a multistep linkage, 19 675 births between 1952 and 1988 were identified as children of a cohort of 9512 fathers who had worked at least one year in British Columbia sawmills where chlorophenate wood preservatives had been used. A nested case-referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Based on the laterality pattern observed (right eye only) in both cases, germ-cell mutation seems more likely (56). In relation to occupation, paternal exposure to dioxin-contaminated chlorophenols in the sawmill setting has been associated with excess congenital cataracts in children born to these workers (57). Connection with the present study is tentative.…”
Section: Birth Defectssupporting
confidence: 59%
“…Based on the laterality pattern observed (right eye only) in both cases, germ-cell mutation seems more likely (56). In relation to occupation, paternal exposure to dioxin-contaminated chlorophenols in the sawmill setting has been associated with excess congenital cataracts in children born to these workers (57). Connection with the present study is tentative.…”
Section: Birth Defectssupporting
confidence: 59%
“…12,13 Unfortunately, the serum dioxin concentrations in the studies of these occupationally exposed fathers were not determined. In our study, the median body concentrations in men and women living in 1976 in the three exposed zones, A, B, and R, was about 20 times the average normal concentration of TCDD in men and women in industrialised countries.…”
Section: Discussionmentioning
confidence: 99%
“…6 Worldwide, the sex ratio at birth in human beings is fairly constant-106 men for every 100 women, or, as is sometimes reported, the male proportion of total births (106 male births divided by 206 total births) is 0·514 (51·4%). 7 Researchers, however, have reported a decreased proportion of male births in the general population in Denmark, 8 Netherlands, 9 USA, 10 Canada, 11 in selected populations such as in sawmill-industry workers who were exposed to trichlorophenate contaminated with various dioxin congeners, 12,13 and in individuals exposed to air pollution from incinerators.…”
Section: Introductionmentioning
confidence: 99%
“…PCP has been classified by the International Agency for Research on Cancer as a Group 2B (possible) human carcinogen [IARC, 1991], while 2,3,7,8-TCDD has been designated a Group 1 human carcinogen on the basis of the evidence of increased risk of all cancers combined, and the other dioxin congeners found in PCP are classified as Group 3 or not classifiable as to their carcinogenicity in humans [IARC, 1997]. Some studies have found limited evidence of a weak effect of chronic occupational PCP exposure on the immune system [Colosio et al, 1993], an association between paternal exposures to PCP in sawmill workers and the development of certain congenital anomalies in offspring [Dimich-Ward et al, 1996], chloracne and certain biochemical abnormalities that persisted years after exposure [Hryhorczuk et al, 1998] and subtle alterations of neurobehavioral performance in women with long-term low exposure to PCP [Peper et al, 1999].…”
Section: Introductionmentioning
confidence: 99%